The Effect of Simplicia Leaves of Papaya (Carica Papaya L) on Adequacy of Breast Milk in Babies Aged 6 Months - Batubara, Novita Sari; Rangkuti, Nur Aliyah; Siregar, Rya Anastasya; Suryani, Elvi; Siregar, Ratna Dewi; Harahap, Maryam Latifah (PT Inovasi Pratama Internasional, 2022)
Adequacy of breast milk is the condition of the baby or mother showing several signs that indicate satisfaction in the production or consumption of breast milk. Infants aged 6 months, can be judged to have adequate breastfeeding, one of which is marked by the baby drinking breast milk every 2-3 hours or in 24 hours at least getting breast milk 8 times in the first 2-3 weeks. Papaya leaf simplicia can be one way to increase the rate of secretion and milk production and a strategy to overcome the failure of exclusive breastfeeding caused by low milk production. Based on this background, the researchers conducted a study on the effect of papaya leaf simplicia (Carica Papaya L.) on the adequacy of breast milk in infants aged 6 months. This type of research is a quasi-experiment with a one-group pretest-posttest design. The results showed that there was an effect of Papaya Leaf Simplicia (Carica Papaya L.) on the adequacy of breast milk in infants aged 6 months (sig=0,000<α=0,05). This shows that consuming Papaya Leaf Simplicia (Carica Papaya L.) is proven to be effective in increasing the adequacy of breast milk.